Submerged hollow fiber membranes : hydrodynamic and fouling study - Yeo, Adrian Piah Song (2010)
Hollow fiber membranes have the advantage of the highest surface area to volume ratio of any type of membrane configuration. This thesis examines the interaction between the filtration performance and the bubble-induced hydrodynamics around submerged hollow fibers as well as physical characteristics such as fiber looseness and aerator configuration. Two non-invasive methods, Particle Image Velocimetry and Phase Contrast X-Ray Microimaging (XMI) were used to characterize shear stresses, fiber movement and fouling. It was found that it was possible to provide the same level of performance with significantly less air flow by using smaller bubbles as opposed to larger ones. The standard deviations of the shear stress, and the acceleration of the fiber showed the best correlation with the performance for the tight fibers and loose fibers respectively. XMI was shown to be very useful for observing bubble formation and fouling within the membrane.